Obstacles and difficulties implementing the lean philosophy in Brazilian enterprises - Caroline Morito Pereira; Rosley Anholon; Antonio Batocchio (Brazilian Journal of Operations & Production Management, 2017)
The success of Lean Manufacturing does not come down only to its application tools; it is an accomplishment of the entire leadership and workers dedicated to putting the system’s essence into practice, along with its underlying values and philosophy. In this context, the main purpose of this study is to present an analytical research in terms of the obstacles and difficulties faced by Brazilian companies to implement the Lean Manufacturing. Through a literature review of the annals of ENEGEP (the Brazilian Production Engineering Conference), this research concluded that the main obstacles and difficulties of such implementation fall under seven lines: 1) difficulties using the tool; 2) operational resistance; 3) cultural differences; 4) slow response to market; 5) lack of top/senior management involvement; 6) lack of middle management support, 7) lack of resources to invest. This article stands as a useful source for further studies about the Lean Manufacturing system.